Reflexive pronoun resolution in Portuguese: testing similarity-based interference - Luegi, Paula; Leitão, Márcio; Avila-Varela, Daniela; Gomes, Jéssica; Costa, Armanda (Frontiers in Language Sciences, 2024)
In the present study, we test whether, during reflexive pronoun resolution, structural cues guide both the language processing system and its underlying memory-based mechanisms or whether the latter might be influenced by non-structural cues as well. Specifically, we explore the inhibitory effects caused by similarity-based interference, which might lead to disruption during reading, reflected in slower reading times and lower accuracy rates. We contrast conditions in which two referents, the reflexive antecedent, and a distractor, are of the same or different gender in sentences with a gender-unmarked reflexive, a gender-marked reinforcement reflexive form, or both. The different types of reflexive constructions allow us to tease apart encoding and retrieval interference since while encoding interference is expected both with gender-marked and gender-unmarked reflexives, retrieval interference is only expected with gender-marked reflexives. In two self-paced reading experiments, one in European Portuguese (EP) and one in Brazilian Portuguese (BP), we find strong and consistent offline results that point towards encoding similarity-based interference. However, the online results only partially support this perspective: In EP, we find encoding interference in the gender-unmarked reflexive and the post-critical regions, while in BP, the effect is only marginally significant in the post-critical region.In addition, in BP, but not in EP, we consistently observe the effects of the participants' accuracy on reading time, with less accurate readers being consistently faster. Overall, our results show that during reflexive pronoun resolution, memory interference can have a negative impact, both during online (reading time) and offline (comprehension accuracy) language processing. With the present study, we contribute to the literature by expanding the set of the tested languages and with more evidence of encoding similarity-based interference, not driven by retrieval cues, on language processing. Moreover, our results are in line with previous studies replicating an asymmetry between robust offline results and elusive online effects. Also, in line with previous studies, our results show that similarity-based interference in grammatical sentences is subtle and might easily be hidden by the large variability between participants (e.g., mean accuracy).